Effect of Temperature Gradient on Compressive Strength and Strain Characteristics of Coarse-Grained Frozen Soil - Jiajun Luo; Changtao Hu; Zhilong Zhang; Bingbing Lei; Jing Luo; Ao Zhang; Ge Hao (Geofluids)
The temperature field beneath a roadbed is asymmetrically distributed, which causes uneven settlement, longitudinal cracking, and even sliding and collapse, as well as other diseases of frozen soil roadbeds. Most roads in alpine mountain regions are half-filled and half-excavated. The degree and direction of the temperature gradient are utilized as variables in a numerical simulation to examine the deformation properties of coarse-grained frozen soil. The findings demonstrate that (1) coarse-grained frozen soil has a nonlinear connection between strength and the lowest temperature, with strength increasing with decreasing temperature and decreasing under the influence of the temperature gradient. (2) When an arbitrary temperature field acts on frozen soil, its monolithic character diminishes, its shear strength and maximum strength decrease as the angle θ increases, and the distribution of the shear zone takes the form of an X. (3) An asymmetrical shear zone forms when the direction of the temperature gradient θ deviates from 0°. The degree of asymmetry in the ground deformation and the angle of inclination of the shear zone are positively related to θ.